2013
DOI: 10.1021/am400140c
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance of Organic Light-Emitting Diodes Fabricated on Al-Doped ZnO Anodes Incorporating a Homogeneous Al-Doped ZnO Buffer Layer Grown by Atomic Layer Deposition

Abstract: In this work, we investigated the use of a homogeneous Al-doped zinc oxide (AZO) buffer layer to improve the performance of an organic light-emitting diode (OLED) device fabricated on an AZO anode. For this, 10-nm-thick AZO buffer layers with Al doping concentrations of 3.1, 4.1, and 5.1 at % were grown on 140-nm-thick AZO anode films containing 2.1 at % Al by atomic layer deposition. The electrical resistivity of the AZO anode with a homogeneous AZO buffer layer decreased with an increase in Al doping concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 29 publications
(39 reference statements)
1
24
0
Order By: Relevance
“…AZO is a transparent conducting oxide (TCO) with reasonable electrical resistivity (~10 −4 Ω cm) and large transmittance (~92%), making it an attractive candidate for transparent conducting electrode in photoelectric devices. It has been demonstrated that an accompanying free electron is paired with the process when a Zn 2+ cation is replaced by an Al 3+ cation, which is responsible for the increased conductivity [39,40,41]. Furthermore, Figure 3c shows the SEM image for the A 3 ZO-NPs obtained by the present chemical precipitation and 500 °C calcination processes.…”
Section: Resultsmentioning
confidence: 93%
“…AZO is a transparent conducting oxide (TCO) with reasonable electrical resistivity (~10 −4 Ω cm) and large transmittance (~92%), making it an attractive candidate for transparent conducting electrode in photoelectric devices. It has been demonstrated that an accompanying free electron is paired with the process when a Zn 2+ cation is replaced by an Al 3+ cation, which is responsible for the increased conductivity [39,40,41]. Furthermore, Figure 3c shows the SEM image for the A 3 ZO-NPs obtained by the present chemical precipitation and 500 °C calcination processes.…”
Section: Resultsmentioning
confidence: 93%
“…Oxide semiconductors and their potential application in next-generation devices have received a great deal of attention due to their various optical, electric, and magnetic properties [1][2][3][4][5][6]. An understanding of the origin of these properties is also very important, for which many studies have employed various analytical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Rutile phase of TiO 2 is more stable than the other two phases and the transformation from anatase and brookite to rutile can be achieved by thermal annealing [5][6][7]. Nanosized TiO 2 has found applications in many fields like gas sensors [8,9] transistors [10], light-emitting diodes (LED) [11], sunscreen [12], field emission devices [13] and solar cells [14]. The properties of TiO 2 most probably depend upon the preparation method.…”
Section: Introductionmentioning
confidence: 99%